Comparative evaluations of bulk seeded protein crystallization in batch versus continuous slug flow crystallizers - Pu, Siyu (2022)
The present work evaluated for the first time the use of continuous slug flow crystallizer (CSFC) in bulk seeded protein crystallization, using lysozyme (LYZ) as the model protein. LYZ crystals pre-prepared in batch crystallizer were used as seeds. The crystallization was performed at supersaturation level below the metastable-zone-limit. The resultant crystal size distribution (CSD), CSD's reproducibility, LYZ's bioactivity, and crystallization efficiency as characterized by the space-time-yield (STY, mg/h·L) were determined. The results showed that the CSFC's performance was governed by the flowrate, where a trade-off existed between crystal quality and crystallization efficiency upon varying the flowrate. At low flowrates, which reduced the shear rate and prolonged the residence time, well-defined large tetragonal crystals were produced attributed to suppressed secondary nucleation and extended crystal growth, but low STY due to difficulty in transporting the seeds/products crystals. Higher flow rates led to higher STY, but increased production of small non-tetragonal crystals that formed agglomerates. Compared to batch crystallizer, the CSFC produced LYZ crystals of similar average size, morphology, and bioactivity, but with roughly 50% lower STY, as the batch's high-shear environment promoted secondary nucleation, hence higher crystallization rate. The CSD's width and reproducibility was nevertheless significantly improved in CSFC.